2log(4)(3y-5)=log(4)(49)

Simple and best practice solution for 2log(4)(3y-5)=log(4)(49) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2log(4)(3y-5)=log(4)(49) equation:


Simplifying
2log(4)(3y + -5) = log(4)(49)

Reorder the terms:
2glo * 4(-5 + 3y) = log(4)(49)

Reorder the terms for easier multiplication:
2 * 4glo(-5 + 3y) = log(4)(49)

Multiply 2 * 4
8glo(-5 + 3y) = log(4)(49)
(-5 * 8glo + 3y * 8glo) = log(4)(49)
(-40glo + 24gloy) = log(4)(49)

Reorder the terms for easier multiplication:
-40glo + 24gloy = 4 * 49glo

Multiply 4 * 49
-40glo + 24gloy = 196glo

Solving
-40glo + 24gloy = 196glo

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-196glo' to each side of the equation.
-40glo + -196glo + 24gloy = 196glo + -196glo

Combine like terms: -40glo + -196glo = -236glo
-236glo + 24gloy = 196glo + -196glo

Combine like terms: 196glo + -196glo = 0
-236glo + 24gloy = 0

Factor out the Greatest Common Factor (GCF), '4glo'.
4glo(-59 + 6y) = 0

Ignore the factor 4.

Subproblem 1

Set the factor 'glo' equal to zero and attempt to solve: Simplifying glo = 0 Solving glo = 0 Move all terms containing g to the left, all other terms to the right. Simplifying glo = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-59 + 6y)' equal to zero and attempt to solve: Simplifying -59 + 6y = 0 Solving -59 + 6y = 0 Move all terms containing g to the left, all other terms to the right. Add '59' to each side of the equation. -59 + 59 + 6y = 0 + 59 Combine like terms: -59 + 59 = 0 0 + 6y = 0 + 59 6y = 0 + 59 Combine like terms: 0 + 59 = 59 6y = 59 Add '-6y' to each side of the equation. 6y + -6y = 59 + -6y Combine like terms: 6y + -6y = 0 0 = 59 + -6y Simplifying 0 = 59 + -6y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 8+3e^3(x)=26 | | 026=24-x | | 7+2x-4=5-x | | 8x+x(2)-7(2)=7x+3x-14 | | (4p^2-2q+5)-(-6-3q+5p^2)=0 | | 6x+3(-6x-6)=66 | | -3(-8-6a)=24+3a | | -61=5x+7(-3x+5) | | 56+x=114 | | 141-8x=10x-21 | | 70.3=b/9 | | x+x+72+x-12=180 | | 6x^3-12x^2-3x+6=0 | | x+x+72+x-20=180 | | 4+3=24c-16 | | 4+3=24 | | 2/6a | | 150-9x=78-x | | 54=atimesb^3 | | 25=5x+2(-2x+8) | | 18=atimesb^2 | | -170=5x+5(-3x-18) | | x^2+19=380 | | (7/x-5)-(7/x)=(35/x^2-5x) | | 2(150-9x)=78-x | | ×/12=24/30 | | 3x+2(x-16)=-92 | | 5x-17=-87 | | 3x+2(x-15)=-91 | | 2(5x+4)=7x+14 | | -6x+12y=120 | | 9.83=4y+3x |

Equations solver categories